How and Why : A Process Evaluation Proposal to Assess the Development Phase of Ergonomic Interventions - Albert, Valérie; Vézina, Nicole; Bilodeau, Henriette; Coutarel, Fabien (Perspectives interdisciplinaires sur le travail et la santé)

(untitled) (Les Amis de PISTES, 2017)
Ergonomic interventions assessed by way of experimental methods appear to be over-simplified when they are limited to a standardized solution for a large number of workers. These interventions differ greatly from interventions provided by ergonomists out in the field who carry out a complex, participatory, change process closely adapted to an organization’s context. In such complex interventions, ergonomists carry out numerous actions before specific work modifications are implemented, but these actions are almost never mentioned in evaluation studies. The goal of this article is to present the methodological framework of a process evaluation focussing on the development phase of complex ergonomic interventions, the development phase occurring prior to the implementation of work modifications. The collection of quantitative and qualitative data in real time through a logbook, document analysis, and semi-structured interviews is proposed. This process evaluation model should provide knowledge of the actions that led to changes in specific contexts and that may represent the transferable aspect of the intervention to future interventions carried out in similar contexts.